2010
DOI: 10.1007/s00431-010-1343-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of a trend towards obesity in preschool children: a longitudinal study

Abstract: The study was planned to determine identifiable starting points of a trend towards obesity and the influence of variables in preschool children aged 0 to 6 years. In this longitudinal follow-up study, 102 children were enrolled. Anthropometric measurements such as weight-height centiles (specific for gender and age group), weight-height growth velocities, and body mass indices were taken annually and compared within each group from birth to 6 years. Family history and lifestyle variables were also recorded and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
(34 reference statements)
8
7
0
Order By: Relevance
“…Our pattern data suggest that having a BMI <17 (or a BMI value increase of <3–4 from birth BMI) in the first 6 months of life distinguished normal weight from obese and morbidly obese children at age 5. Other studies have shown the earlier that BMI increases by 3 or more values from birth BMI, the more likely the child will be overweight later in the life course . Our findings concur with those of Taveras et al ., who showed that children who gained excessive weight in the first 6 months of life, as measured by crossing more than two weight‐for‐length percentile lines on the CDC growth charts, had the highest risk of being obese at 5 years .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our pattern data suggest that having a BMI <17 (or a BMI value increase of <3–4 from birth BMI) in the first 6 months of life distinguished normal weight from obese and morbidly obese children at age 5. Other studies have shown the earlier that BMI increases by 3 or more values from birth BMI, the more likely the child will be overweight later in the life course . Our findings concur with those of Taveras et al ., who showed that children who gained excessive weight in the first 6 months of life, as measured by crossing more than two weight‐for‐length percentile lines on the CDC growth charts, had the highest risk of being obese at 5 years .…”
Section: Discussionsupporting
confidence: 93%
“…A study of pre‐school children revealed that rapid and consistently sequential increases in weight, height and BMI patterns from 6 months to 1 year suggested development of later obesity. An early and rapid increase in body weight in the first 12 months has been significantly correlated with high BMI at age 12 and as adults . Our data are somewhat similar; we found that a BMI trajectory indicating obesity was detectable between the cohorts as early as 15 months and persisted at every observation up to 5 years ( F 3,202 = 6.322, P = 0.046), suggesting that increased BMI in the first year may be an early warning sign of later obesity just as growth patterns between 2 and 4 years of age are …”
Section: Discussionsupporting
confidence: 77%
“…Family history of obesity was also found to be associated with obesity in this study. In agreement with this, Yücel et al reported that paternal obesity and having an obese sibling were significant risk factors for excess BMI (12). These findings support the need to promote active living among young generations to control the increasing rate of obesity especially among those with positive family history.…”
Section: Discussionmentioning
confidence: 55%
“…9,[17][18][19] First-year weight gain in low-birth-weight infants also predicted the development of obesity by 8 years of age. 20 Appropriate weight-for-gestational age children who displayed rapid weight gain in infancy had a greater risk of being overweight or obese during childhood than children who did not experience rapid weight gain post-birth.…”
Section: Obesity Trends In Early Lifementioning
confidence: 99%
“…21 Rapid and consistently sequential increases in weight, height, and BMI patterns from 6 months to 1 year were associated with the development of later obesity. 19 Children who have rapid weight gain in infancy have growth trajectories that diverge from normal growth around 6 months of age. By 7 years, these children have 6.2 times higher BMIs (95% CI), 2.4 times greater fat mass (P = 0.0002), and 16.5 times higher overweight/obese weight statuses (P = 0.0002) than children who did not have rapid infancy weight gain.…”
Section: Obesity Trends In Early Lifementioning
confidence: 99%